Representation of Marxism in Vampires in Havana - Kariko, Abdul Aziz Turhan (Bina Nusantara University, 2011)
Article presents an animated film related to ideological development in Cuba. This effort brings an understanding of ideology and cultural policy of Cuba as a communist state. Presentation begins with summary of the story, history and background, ideological concepts, and the movie Vampires in Havana itself. It is concluded that the film represents ideological disputes between capitalism and Marxism in Cuba, as well as giving an ideal perspective on how the world should work.